Morphology controlled synthesis of polyaniline nanostructures using swollen liquid crystal templates. Issue 18 (21st April 2014) - Dutt, Sunil; Siril, Prem Felix
ABSTRACT Preparation of zero‐dimensional and one‐dimensional nanostructures of polyaniline (PANI) were achieved by using swollen liquid crystals (SLCs) as 'soft' templates. The monomer (aniline) was first entrapped in SLCs by replacing the oil phase (cyclohexane) with a mixture of aniline and cyclohexane. Zero‐dimensional nanostructures of PANI were obtained by thorough mixing of APS with the mesophases. One‐dimensional nanostructures were prepared by allowing slow diffusion of APS through the mesophase. PANI nanostructures were extracted from the mesophase and were characterized by UV‐visible spectroscopy, FTIR spectroscopy, powder X‐ray diffraction, atomic force microscopy, scanning electron microscopy (SEM), and conductivity measurements. A plausible mechanism for the formation of the nanostructures has been proposed. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40800.